Coinfection of insect cells with recombinant baculovirus expressing pp60v-src results in the activation of a serine-specific protein kinase pp90rsk. - Vik, T A (1990)
A recombinant baculovirus was constructed for the production of the serine-specific protein kinase, pp90rsk (where rsk is ribosomal S6 kinase), in insect cells. The Xenopus pp90rsk expressed in the infected cells had nearly undetectable enzyme activity in contrast to the same enzyme coproduced with the v-src oncogene product pp60v-src. The transforming gene product pp60v-src very effectively activated pp90rsk, whereas the products of c-src and the myristoylation-minus nontransforming virus NY315 were markedly less effective. Only a fraction of the total pp90rsk population was activated, and it could be partially separated from unactivated protein by ion-exchange chromatography. When compared to the unactivated form, the activated enzyme displayed about a 4000-fold increase in the capacity to phosphorylate the ribosomal protein S6. The enhanced enzymatic activity appeared to be due to phosphorylation of pp90rsk.